Thermal Parameters Analysis During Directional Solidification Of Al-Cu Eutectic Alloys - Kociubczyk, Alex Iván (2014)
Al-Cu eutectic alloy samples (Al-33.2wt.%Cu) were solidified directionally upward under conditions which produce the columnar-to-equiaxed transition (CET) phenomenon. The position of the CET was located in each sample and the distance from the bottom of the ingot was measured. During solidification the distribution of temperatures were measured by means of thermocouples located strategically. From the measured temperatures the following parameters were obtained; local temperature gradient, cooling rate of the liquid and solid and growth rate. Three different velocities of heat extraction were employed and the temperature gradient reaches values of 2.1 ºC/cm, 0.1 °C/cm and -4.3ºC/cm, respectively. The results are presented and discussed comparing with the results obtained in the case of CET in dendritic Al-Cu alloys